An insight on the N-glycome of notochordal cell-rich porcine nucleus pulposus during maturation. - Günay, Büşra; Matthews, Elizabeth; Morgan, Jack; Tryfonidou, Marianna A; Saldova, Radka; Pandit, Abhay (John Wiley and Sons Inc., 2023)
Degeneration of the intervertebral disc is an age-related condition. It also accompanies the disappearance of the notochordal cells, which are remnants of the developmental stages of the nucleus pulposus (NP). Molecular changes such as extracellular matrix catabolism, cellular phenotype, and glycosaminoglycan loss in the NP have been extensively studied. However, as one of the most significant co- and posttranslational modifications, glycosylation has been overlooked in cells in degeneration. Here, we aim to characterize the N-glycome of young and mature NP and identify patterns related to aging. Accordingly, we isolated N-glycans from notochordal cell-rich NP from porcine discs, characterized them using a combined approach of exoglycosidase digestions and analysis with hydrophilic interaction ultra-performance liquid chromatography and mass spectrometry. We have assigned over 300 individual N-glycans for each age group. Moreover, we observed a notable abundance of antennary structures, galactosylation, fucosylation, and sialylation in both age groups. In addition, as indicated from our results, increasing outer arm fucosylation and decreasing α(2,3)-linked sialylation with aging suggest that these traits are age-dependent. Lastly, we have focused on an extensive characterization of the N-glycome of the notochordal cell-rich NP in aging without inferred degeneration, describing glycosylation changes specific for aging only. Our findings in combination with those of other studies, suggest that the degeneration of the NP does not involve identical processes as aging.
Keywords: N-glycosylation; aging; intervertebral disc degeneration; liquid chromatography-mass spectrometry; notochordal cells; nucleus pulposus; Molecular Medicine; Biochemistry, Genetics and Molecular Biology (miscellaneous); Physiology; Cancer Research; SDG 3 - Good Health and Well-being